Faktor-Faktor yang Mempengaruhi Keberhasilan ASI Eksklusif pada Anak di RSUD Wangaya - Kurnia, Bella; Suryawan, I Wayan Bikin (Majalah Kedokteran Indonesia, 2019)
Background: Breastmilk is the best natural food for babies. Human milk consists of nutrients, such as proteins, lipid, carbohydrate, minerals, vitamins, and trace elements that are important for babies to ensure optimum growth and development. There is still low percentage of breastfeeding coverage in Indonesia. This study was designed to determine the factors that associated with the success of exclusive breastfeeding of children at Wangaya General Hospital. Methods: This study uses case-control method. Data was collected from medical record and interviews in Wangaya Regional General Hospital between April to May 2019. This study uses consecutive sampling. Data analysis uses chi square for bivariate and logistic regression for multivariate. Results: Factors associated with the success of exclusive breastfeeding were multipara (p=1,000; OR=1.214), labor method (p=1,000; OR=1.214), information availability (p less than 0,001; OR=46.000), occupation (p=0,148; OR=2.778), and educational level (p=0,240; OR=2.364). From multivariate analysis, information availability (p=0,001) was significant. Conclusion: Factor associated with successful breastfeeding in children at Wangaya General Hospital was information availability about breastfeeding to the mother.